Effect of silicon on recrystallisation of V–Ti microalloyed steel. (February 2014) - Wu, D. Y.; Pei, J. P.; Gong, Y. L.; Fan, W. B.; Xiao, F. R.; Liao, B.
<x content-type="archive" xml:space="preserve">Abstract</x> The dynamic recrystallisation (DRX) and static recrystallisation (SRX) behaviours of three V–Ti microalloyed steels were studied by the analysis of the true stress–strain curves and the stress relaxation curves under different deformation conditions. The results of DRX showed that deformation activation energy Qdef, peak stress and peak strain increased, as a result of the solute strengthening and dragging effect due to Si. The results of SRX showed that Si increased the SRX activation energy QSRX. The solute retardation parameter for static recrystallisation of Si was calculated. Based on the SRX results, to quantify the drag effect of Si and V, a new model was proposed to describe the time for 50% recrystallisation (t0·5), which was tested and verified by previously published data on similar steels. Precipitation during recrystallisation could lead to a lower value of the Avrami exponent.